WANITA BERHIJAB MEROKOK DALAM SUDUT PANDANG REALIAS SOSIAL - Mirza Azkia Muhammad Adiba (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2023)
Regarding women discussing the topics discussed in this study, hooded women are identical to women who are Muslim, women are good, close their genitals, dress modestly, and be polite. More respected by men because of the hooded woman. In Islam, a woman who wears a veil up to the back, wears a robe and her chest is closed. In this study, researchers used a qualitative descriptive research method, descriptive research in general carried out to see events that attracted the attention of researchers. Descriptive topics of systematic discussion and accurate and characteristic facts about participants or about a particular field. The data collected is eye-only, so no one is looking for an explanation, proposed a hypothesis, predicts or engages an implication. This research resulted in not agreeing and was negative for veiled women who smoke, the reason taken generally because the veil in women is a symbol of Muslim women. The speakers are also responsible if there are hooded women who smoke, including things that are done publicly openly.